Efficacy of Low Molecular Heparin on Preeclampsia by Inhibiting Apoptosis of Trophoblasts via the p38MAPK Signaling Pathway. (3rd August 2021) - Quan, Dandan; Li, Li; Zuo, Manzhen
Abstract : Objective . To explore the efficacy of low molecular heparin on preeclampsia by inhibiting apoptosis of trophoblasts via the p38MAPK signaling pathway. Methods . A preeclampsia rat model was established, and the effects of low molecular heparin on preeclampsia via the p38MAPK signaling pathway were analyzed based on intervention of the rats with different combinations of low molecular heparin and p38MAPK signaling pathway activator. Furthermore, a hypoxia/reoxygenation model of trophoblasts in vitro was established to explore the effects of low molecular heparin on trophoblasts via the p38MAPK signaling pathway. Results . After treatment with low molecular heparin, pregnant rats in the heparin group showed significantly decreased blood pressure, 24 h proteinuria, and p38MAPK protein levels in placenta tissues and decreased apoptosis rate of placenta tissue cells (all P < 0.05 ) and showed more fetal rats and lowered weight of them (both P < 0.05 ) but showed no significant change in the weight of placenta (all P > 0.05 ). Pregnant rats treated with low molecular heparin and p38MAPK activator showed significantly higher blood pressure, 24 h proteinuria, and p38MAPK protein levels in placenta tissues and apoptosis rate of placenta tissue cells than those of pregnant rats in the heparin group (all P < 0.05 ) and also showed less fetal rats and lighter fetal rats than those in the heparin group (both P < 0.05 ) but showed no difference with them in the weight of placenta (P > 0.05 ). Further analysis revealed that low molecular heparin could protect the survival and migration of trophoblasts under hypoxia/reoxygenation conditions and reduce apoptosis of them (all P < 0.05 ). Conclusion . Low molecular heparin can alleviate preeclampsia by inhibiting the p38MAPK signaling pathway and can inhibit apoptosis of trophoblasts and promote proliferation and migration of them.